Needle-free dermal delivery of a diphtheria toxin CRM197 mutant on potassium-doped hydroxyapatite microparticles - Weissmueller, N; Schiffter, H; Carlisle, R; Rollier, C; Pollard, A (American Society for Microbiology, 2015)
Injections with a hypodermic needle and syringe (HNS) are the current standard of care globally, but the use of needles is not without limitation. While a plethora of needle-free injection devices exist, vaccine reformulation is costly and presents a barrier to their widespread clinical application. To provide a simple, needle-free, and broad-spectrum protein antigen delivery platform, we developed novel potassium-doped hydroxyapatite (K-Hap) microparticles with improved protein loading capabilities that can provide sustained local antigen presentation and release. K-Hap showed increased protein adsorption over regular hydroxyapatite (P < 0.001), good structural retention of the model antigen (CRM197) with 1% decrease in α-helix content and no change in β-sheet content upon adsorption, and sustained release in vitro. Needle-free intradermal powder inoculation with K-Hap-CRM197 induced significantly higher IgG1 geometric mean titers (GMTs) than IgG2a GMTs in a BALB/c mouse model (P < 0.001) and induced IgG titer levels that were not different from the current clinical standard (P > 0.05), namely, alum-adsorbed CRM197 by intramuscular (i.m.) delivery. The presented results suggest that K-Hap microparticles may be used as a novel needle-free delivery vehicle for some protein antigens.